2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR) 2018
DOI: 10.1109/vr.2018.8446226
|View full text |Cite
|
Sign up to set email alerts
|

Light Virtual Reality Systems for the Training of Conditionally Automated Vehicle Drivers

Abstract: In conditionally automated vehicles, drivers can engage in secondary activities while traveling to their destination. However, drivers are required to appropriately respond, in a limited amount of time, to a take-over request when the system reaches its functional boundaries. In this context, Virtual Reality systems represent a promising training and learning tool to properly familiarize drivers with the automated vehicle and allow them to interact with the novel equipment involved. In this study, the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…There were 52 studies involving at least one of the above items. Three of the studies reported four of these items [93][94][95], and 1 study reported five of these items [88]. Most of the studies gave positive results, but there were also some with negative feedback, especially for both "controllability" (n = 5) and "discomfort" (n = 9).…”
Section: Resultsmentioning
confidence: 99%
“…There were 52 studies involving at least one of the above items. Three of the studies reported four of these items [93][94][95], and 1 study reported five of these items [88]. Most of the studies gave positive results, but there were also some with negative feedback, especially for both "controllability" (n = 5) and "discomfort" (n = 9).…”
Section: Resultsmentioning
confidence: 99%
“…For example, particular real-world situations that would be difficult to find, or replicate, can be modeled in VR, and even replicated as digital twins. Sportillo et al (2018b) explored different educational simulators, and found that the acquisition of driving skills in conditionally automated vehicles was most highly rated for the VR solution, as compared to a user manual and a fixed-base simulator. Driving training in the context of mixed traffic might be especially useful for driving learners who have to consider cooperative driving situations with vehicles of different automation level, and driving simulators can help them achieve this paradigm shift (Sportillo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also used different methods of training such as Augmented Reality (AR) and shown that as compared to owner's manual, AR training lead to higher trust, lower ADAS interaction errors and higher user experience. Two studies by Sportillo et al (2018a) and Sportillo et al (2018b) used Virtual Reality (VR) as a training method and found that overall, VR method led to quick responses, and higher user experience.…”
Section: Introductionmentioning
confidence: 99%